Transcriptomics and differential gene expression in Whitmania pigra (Annelida: Clitellata: Hirudinida: Hirudinidae): Contrasting feeding and fasting modes - Khan, Muhammad Salabat (Ecol Evol, 2019)
The medicinal utility of leeches has been demonstrated through decades of use in modern hospital settings, mainly as relievers of venous congestion following flap or digit replantation surgery. In the present study, we sequence and annotate (through BLAST‐ and Gene Ontology‐based approaches) the salivary transcriptome of the nonblood feeding hirudinid Whitmania pigra and assess the differential gene expression of anticoagulation factors (through both quantitative real‐time PCR [qRT‐PCR] and in silico‐based methods) during feeding and fasting conditions. This was done in order to evince the diversity of putative anticoagulation factors, as well as estimate the levels of upregulation of genes immediately after feeding. In total, we found sequences with demonstrated orthology (via both phylogenetic analyses and BLAST‐based approaches) to seven different proteins that have previously been linked to anticoagulatory capabilities—eglin C, bdellin, granulin, guamerin, hyaluronidase, destabilase I, and lipocalin. All of these were recovered from leeches both in the fasting and in the feeding conditions, but all show signs of upregulation in the feeding leeches. Interestingly, our RNA‐seq effort, coupled with a hypergeometric test, indicated that the differentially expressed genes were disproportionately involved in three main immunological pathways (endocytosis, peroxisome regulation, and lysosome regulation). The results and implications of the finding of anticoagulants in this nonblood feeding leech and the putative upregulation of anticoagulation factors after feeding are briefly discussed in an evolutionary context.